Can the agricultural AquaCrop model simulate water use and yield of a poplar short‐rotation coppice?. Issue 6 (16th February 2017) - Horemans, Joanna A.; Van Gaelen, Hanne; Raes, Dirk; Zenone, Terenzio; Ceulemans, Reinhart
Abstract: We calibrated and evaluated the agricultural model AquaCrop for the simulation of water use and yield of a short‐rotation coppice (SRC) plantation with poplar ( Populus ) in East Flanders (Belgium) during the second and the third rotation (first 2 years only). Differences in crop development and growth during the course of the rotations were taken into account during the model calibration. Overall, the AquaCrop model showed good performance for the daily simulation of soil water content ( R 2 of 0.57–0.85), of green canopy cover ( R 2 > 0.87), of evapotranspiration (ET; R 2 > 0.76), and of potential yield. The simulated, total yearly water use of the SRC ranged between 55% and 85% of the water use of a reference grass ecosystem calculated under the same environmental conditions. Crop transpiration was between 67% and 93% of total ET, with lower percentages in the first than in the second year of each rotation. The observed (dry mass) yield ranged from 6.61 to 14.76 Mg ha −1 yr −1 . A yield gap of around 30% was observed between the second and the third rotation, as well as between simulated and observed yield during the third rotation. This could possibly be explained by the expansion of the understory (weed) layer; the relative cover of understory weeds was 22% in the third year of the third rotation. The agricultural AquaCrop model simulated total water use and potential yield of the operational SRC in a reliable way. As the plantation was extensively managed, potential effects of irrigation and/or fertilization on ET and on yield were not considered in this study. Abstract : User‐friendly and reliable models are needed to accurately estimate water use, biomass production, and the generated energy of short‐rotation coppice plantations under different environmental conditions. This study focuses on water use and biomass production of poplars in bioenergy plantations and shows that the agricultural model AquaCrop can be used as a complement for the more complex process‐based forest models that have been used so far. AquaCrop can reliably simulate evapotranspiration (calibrated with eddy covariance data) and potential yield of a poplar short‐rotation coppice plantation. It can also detect yield gaps caused by the management or by environmental problems.